114 Identification of factors impacting recurrence in patients treated for borderline ovarian tumors: a focus on radicality and minimally-invasive approach. (13th November 2020) - Longo, M; Oltolina, N; Lembo, A; Dri, M; La Motta, G; Granato, V; Ghezzi, F; Casarin, J
Abstract : Introduction: To compare oncological outcomes and disease-free survival (DFS) of patients with borderline ovarian tumors (BOTs) treated via laparotomy (LPT) vs. laparoscopy (LPS) and to evaluate the impact of the different radicalities of treatment on DFS. Methods: This is a retrospective analysis of 128 consecutive patients who underwent LPS (n= 84) and LPT (n= 44) for apparent early-stage BOTs from 2004 to 2019. Seventy (54.68%) have been treated with radical surgery and 58 (45.32%) with fertility-sparing (FS) treatment. Factors associated with recurrence were investigated. Disease-free survival curves were compared with Kaplan-Meier analysis. Results: When comparing LPS vs. LPT, median age at surgery was 45.5 vs. 59 (p <0.001). With a median of follow up of 84.7 months (range:2.7–348.8), 14 patients (10.94%) recurred: 10/14 (64.28%) and 4/14 (28.57%) had ovarian and peritoneal relapse, respectively. Only 3/14 of the recurred patients had malignant transformation (21.45%). Factors such as surgical approach (LPS vs. LPT), histotype and extra ovarian surgery did not impact on recurrence (p-values=NS). Conservative treatment (vs. radical surgery) was associated with recurrence (p=0.01) and unfavorable 5-year DFS (Log-Rank = 0.01), while no impact of the surgical approach on DFS was found (LPS vs. LPT; Log-Rank =0.32). Conclusions: Patients who underwent FS surgery for BOTs had higher risk of recurrence and unfavorable disease-free survival compared to those who had radical treatment, while surgical approach did not negatively impact on survival. A strict follow-up should be recommended for early detection of potential recurrences.